Gorham-Stout disease: a textbook presentation of a rare disease in Pakistan - Muhammad Ibrahim,; Muhammad Usman,; Hawwa Khan,; Faryal Javaid,; Maria Tasneem,; Zeeshan Khan, (Journal of the Pakistan Medical Association, 2025)
Gorham-Stout disease is an exceptionally rare disease which is characterised by massive osteolysis of the bone, oedema, and in severe cases pleural effusion and chylothorax. Its aetiopathology is unknown, and no specific treatment has been modulated thus far. We report the case of a 17-year-old male with osteolysis in the bones of his entire left arm and persistent chylothorax. Due to the late presentation and patient’s desire for a better quality of life, amputation was the only choice left for treatment. This case was evaluated and treated at the Orthopaedic Surgery and Trauma department of Rehman Medical Institute in Peshawar, Pakistan. Key words: Gorham Stout Syndrome, Massive osteolysis, Rare disease.